Beliefs and Values About Music in Early Childhood Education and Care: Perspectives From Practitioners - Barrett, Margaret S.; Flynn, Libby M.; Brown, Joanne E.; Welch, Graham F. (Frontiers in Psychology, 2019)
This paper reports the findings of a study that aimed to identify the music beliefs and values of educators in early childhood education and care settings in Australia. The aims of the study were two-fold: to adapt and pilot a survey of music beliefs and values which might be implemented subsequently nationally in childcare settings; and, secondly, to identify the music beliefs and values held by early childhood and care educators concerning music in children’s learning. The research questions that guided this component of the study were: What is the profile of early childhood and care educators? What beliefs and values for music engagement are held by early childhood and care educators? What shapes early childhood and care educators’ music beliefs and values? Findings indicated that educators’ beliefs and values on all items are above the mid-point indicating overall positive attitudes towards music despite the majority having no formal qualifications in music or a history of instrumental performance and/or singing. Given the overall positive attitudes towards music we suggest there is enormous potential within this population for further professional learning and development targeted at music and its potential wider benefits in young children’s learning and lives.